2016
DOI: 10.1111/jog.13174
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fetal myocardial performance index in women with pregestational and gestational diabetes mellitus

Abstract: We conclude that fetuses of diabetic mothers have significant left ventricular systolic and diastolic dysfunction. MPI may be used in the prediction of adverse perinatal outcome in diabetic pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 33 publications
8
52
0
Order By: Relevance
“…Other studies suggested that the MPA index has a more stable pattern with advancing gestation . Fetuses of diabetic mothers usually have a higher value for the MPI at all trimesters compared to controls . Although these results support impairment in both systolic and diastolic components of cardiac cycle in fetuses of diabetic mothers, some studies could not reveal any changes in the MPI index or E/A ratio in fetuses of diabetic mothers …”
Section: Functional Evaluationmentioning
confidence: 77%
See 3 more Smart Citations
“…Other studies suggested that the MPA index has a more stable pattern with advancing gestation . Fetuses of diabetic mothers usually have a higher value for the MPI at all trimesters compared to controls . Although these results support impairment in both systolic and diastolic components of cardiac cycle in fetuses of diabetic mothers, some studies could not reveal any changes in the MPI index or E/A ratio in fetuses of diabetic mothers …”
Section: Functional Evaluationmentioning
confidence: 77%
“…This may be attributed to the already lower E/A ratio that exists in fetuses of diabetic mothers at early gestation, as supported by studies evaluating the E/A ratio in the first trimester . Many other studies have also found a lower E/A ratio in fetuses of diabetic mothers compared with those of nondiabetic mothers in the second and third trimesters . At the same time, the E/A ratio can be measured lower in fetuses of diabetic mother compared to healthy controls even if blood glucose level is well regulated .…”
Section: Functional Evaluationmentioning
confidence: 82%
See 2 more Smart Citations
“…MPI levels are expected to change in the presence of pathological conditions that influence fetal cardiac functions. These include fetal growth restriction (FGR), twin‐twin transfusion syndrome, maternal diabetes mellitus, preeclampsia, fetal hydrops, and fetal anemia . When fetal cardiac functions influence the MPI, it may be important to decide the time of the birth.…”
Section: Introductionmentioning
confidence: 99%